Photo Souvenir - Cohen, Paul; Van Haalen, Martijn (CPS Films/VPRO TV, 2006)
Verzio FF submission n the 60s and 70s, Philippe Koudjina, who was born in Benin and now lives in Niamey, Niger, was a much loved and popular photographer. Today, the almost blind man sits daily in his wheel chair next to the main street and greets the people passing by, whom he photographed during the euphoric times of independence. His black and white photos show people dancing the Twist to rock and roll music and enthusiastically embracing themselves. These documents of his time have artistic value nowadays. While similar photographs of other African photographers gain high prices in art metropolises like New York and Paris (for example: Malick Sidibé, Golden Lion, Venice Biennale, 2007), Koudjina’s work remains unknown. “Photo Souvenir” questions the exclusiveness of the international market. It asks: Which aspects of Koudjina´s photography are relevant in order to give his work recognition in the western world? Away from Koudjina's daily life, we follow two French art connoisseurs who try to offer his photographs to the French galerie: agnes b.